The modern architectural landscape - Constant, Caroline (University of Minnesota Press, 2012)
" In The Modern Architectural Landscape Caroline Constant examines diverse approaches to landscape in the work of architects practicing in Europe and the United States between 1915 and the mid-1980s. Case studies highlight landscapes in the public realm rather than the private garden, which had been a primary focus of much Western landscape theory and practice during the early decades of the century. These landscapes do more than accommodate the functional needs of the evolving mass society in parks, playgrounds, and places of assembly; they give formal expression to Modern Movement social and political ideologies, engaging the symbolic potential of the modern landscape--particularly in its ability to take on new, more democratic forms of social organization. Constant probes the cultural significance of specific landscapes designed by architects, understanding them as ways of interpreting the world and the place of humankind in the world. The examples she scrutinizes extend widely across the century (from the works of Erik Gunnar Asplund and Jože Plečnik to those of Le Corbusier and Rem Koolhaas) and around the globe (from suburban Los Angeles to Barcelona and Chandigarh).Approaching landscape as an essential component of modern architecture's constructive endowment of material with social value, The Modern Architectural Landscape focuses on the precise material forms and ideological underpinnings of landscapes conceived by architects, revealing them as salient to the formulation of both modern architecture and the modern landscape. "--